One world one burn rehabilitation standard. Issue 5 (August 2016) - Serghiou, M.A.; Niszczak, J.; Parry, I.; Li-Tsang, C.W.P.; Van den Kerckhove, E.; Smailes, S.; Edgar, D.
Highlights: Examine similarities and differences in burn rehabilitation around the world. Develop essential burn rehabilitation practice guidelines/standards across the globe. Assist in the development of burn rehabilitation programs globally. Abstract: According to the World Health Organization (WHO) burns are a huge global health problem resulting in death and devastation to those who survive large burns as they are faced with significant functional limitations that prevent purposeful and productive living. Members of the International Society for Burn Injuries (ISBI) Rehabilitation Committee conducted a needs assessment survey in order to characterize how burn rehabilitation is implemented worldwide and how the international burn rehabilitation community can help improve burn rehabilitation in identified geographic locations which need assistance in rehabilitating burn survivors successfully. The results of this survey indicated that poor and in some cases resource limited environments (RLEs) around the world seem to lack the financial, educational and material resources to conduct burn rehabilitation successfully. It appears that there are vast discrepancies in the areas of education, training and capacity to conduct research to improve the care of burn survivors as evidenced by the variation in responses between the RLEs and developed countries around the globe. In some cases, the problem is not knowledge, skill and ability to practice burn rehabilitation, but rather having the resources to do so due to financial difficulties.